2011
DOI: 10.1111/j.1742-7843.2011.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Sertraline-induced [Ca2+]i Rise in Human PC3 Prostate Cancer Cells

Abstract: -free medium, pre-treatment with the endoplasmic reticulum Ca 2+ pump inhibitor thapsigargin or 2,5-di-(t-butyl)-1,4-hydroquinone nearly abolished sertraline-induced Ca ] i rises by causing phospholipase C-dependent Ca 2+ release from the endoplasmic reticulum and via multiple Ca 2+ influx pathways that involve store-operated Ca 2+ channels. Sertraline also induced apoptosis that was not triggered by [Ca 2+ ] i rise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…An inhibition of Ca 2+ channels mediated by sertraline has also been reported in excitable cells [6], but its effect on these channels seems to be different in other cell types [12]. Several studies [9, 11, 12] found that it can induce an influx of Ca 2+ via store-operated Ca 2+ channels in nonexcitable cells. An additional effect of sertraline was recently described in human platelets, where it caused a reduction in glutamate uptake [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An inhibition of Ca 2+ channels mediated by sertraline has also been reported in excitable cells [6], but its effect on these channels seems to be different in other cell types [12]. Several studies [9, 11, 12] found that it can induce an influx of Ca 2+ via store-operated Ca 2+ channels in nonexcitable cells. An additional effect of sertraline was recently described in human platelets, where it caused a reduction in glutamate uptake [10].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, considering a sertraline incubation of 24 h, cytotoxicity was observed from 20  µ M in human prostate-cancer cells (PC3) [12] as well as in osteosarcoma cells (MG63) (Lin et al, 2013), from 25  µ M in a human hepatoma cell line (HepG2) [13], from 30  µ M in human platelets [10], and from 37.5  µ M in rat primary hepatocytes [2]. Additional evidence regarding sertraline toxicity has been reported in some organisms, such as the parasite Leishmania donovani [33], fish, and aquatic invertebrates [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sertraline was shown to induce cytotoxicity in a human osteosarcoma cell line [238], a human prostate cancer cell line [239] and a squamous oral cancer cell line [240] by mediating phospholipase C -dependent Ca++ release from the endoplasmic reticulum, ER, and Ca++ cell entry by L-type Ca++ channels. Inhibition of proliferation by sertraline of colon cancer cell lines, both in vitro and when xenografted, was traced to Bcl-2 inhibition [241].…”
Section: Introductionmentioning
confidence: 99%